2012
DOI: 10.1111/j.1600-079x.2011.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of melatonin on the lipopolysaccharide‐induced CC chemokine expression in BV2 murine microglial cells are mediated by suppression of Akt‐induced NF‐κB and STAT/GAS activity

Abstract: Melatonin influences sleep and circadian rhythm, and it has anti-inflammatory functions. However, the mechanism of its anti-inflammatory roles is not well understood. In our studies, we show that melatonin blocked lipopolysaccharide (LPS)-induced CCL2 (monocyte chemotactic protein-1; MCP-1), CCL5 (Regulated upon Activation, Normal T-cell Expressed, and Secreted), and CCL9 (macrophage inflammatory protein-1γ) chemokine mRNA expression in BV2 murine microglial cells. Melatonin markedly inhibited LPS-induced Akt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 58 publications
1
37
0
3
Order By: Relevance
“…Melatonin reduces nf-κB binding in spleen [89]. a number of laboratories report melatonin-induced inhibition of nK-κB activity or inhibition of nf-κB activation [90][91][92][93][94][95][96][97][98][99][100]. these results suggest an interaction of melatonin and the ubiquitin-proteasome system in the activation of nf-κB.…”
Section: Melatonin/ubiquitin Interaction In Brown Fatmentioning
confidence: 49%
“…Melatonin reduces nf-κB binding in spleen [89]. a number of laboratories report melatonin-induced inhibition of nK-κB activity or inhibition of nf-κB activation [90][91][92][93][94][95][96][97][98][99][100]. these results suggest an interaction of melatonin and the ubiquitin-proteasome system in the activation of nf-κB.…”
Section: Melatonin/ubiquitin Interaction In Brown Fatmentioning
confidence: 49%
“…For example, a previous study found that treatment with 1 mM melatonin for 24 h inhibited activation of NF-κB in the human prostate cancer LNCaP cell line (21). In addition, several prior reports have revealed that melatonin inhibits NF-κB activity (34,35), supporting the hypothesis that melatonin is a proteasome inhibitor and a natural NF-κB inhibitor. NF-κB inhibition serves an important role in the treatment of leukemia and lymphoma (36).…”
Section: Discussionmentioning
confidence: 66%
“…96 A nivel molecular, la MEL inhibe la expresión del ARNm de quimiocinas como CCL2 (MCP-1), CCL5 y CCL9 (MIP-1γ) inducidas por LPS en una línea celular de microglia. 97 Este efecto fue mediado por la inhibición de la actividad transcripcional de NF-κB y STAT/GAS. 97 En cultivos organotípicos de cerebro de ratón 98 y de hipocampo de rata 44 estimulados con los pép-tidos Aβ1-40 y Aβ25-35, respectivamente, la MEL disminuye la secreción de citocinas pro-inflamatorias y previene la activación de la microglia y de los astrocitos que se inducen por la exposición al péptido Aβ25-35.…”
Section: La Melatonina Tiene Efectos Anti-inflamatorios En El Sistemaunclassified